KNOWLEDGE OF THE PAST THROUGH ARCHIVES’ WORLD… (DEDICATED TO THE 80TH ANNIVERSARY OF HISTORIAN AND ARCHIVIST G.I. KAKAGASANOV) - Kajmarazova, Lejla Ganievna (History, Archeology and Ethnography of the Caucasus, 2019)
The Institute of history, archeology and ethnography of Daghestan science center of Russian academy of sciences has its own tradition to congratulate scientist with their anniversaries. The main biographical events of Gadjikurban Ibragimovich Kakagasanov, who is a famous Daghestan scientist, historian and archivist, were overviewed in the article. Author also writes about his main achievements in science and his way from being a student of Moscow state university of history and archive to becoming a director of science subdivision of leading scientific research institute of Dagyestan science center of Russian academy of sciences. Kakagasanov’s name is well known not only in science community, but also in wide circle of readers due to his scientific and documental publications dedicated to the newest period of Daghestan history, historiographical and source studies researches that were made under his guidance and also his participation in different science events’ organization and holding and science knowledge’s popularization.